2021
DOI: 10.3389/fonc.2021.683475
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Prognostic Nomogram for Patients With Locoregionally Advanced Nasopharyngeal Carcinoma Incorporating TNM Stage, Post-Induction Chemotherapy Tumor Volume and Epstein-Barr Virus DNA Load

Abstract: ObjectivesTo establish and validate an effective nomogram to predict clinical outcomes for patients with locoregionally advanced nasopharyngeal carcinoma (LA-NPC).Materials and MethodsThe clinicopathological parameters and follow-up information of 402 locoregionally advanced NPC patients (training cohort, n = 302; validation cohort, n = 100) were retrospectively enrolled. The nomogram was built with the important prognostic variables identified by Cox regression analysis. Overall survival (OS) and progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Intensity‐modulated radiation therapy (IMRT) was administered to all patients. Detailed treatment information were previously reported 13 and presented in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Intensity‐modulated radiation therapy (IMRT) was administered to all patients. Detailed treatment information were previously reported 13 and presented in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, IC regime failed to be an independent prognostic factor for survival outcomes. Additionally, all regimens included in this study (TPF, TP, PF, GP) were platinum-based and recommended according to the guideline, which have been widely used in many hospitals 16 , 18 , 21 . Second, the data from a single institution do not provide robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed measurement of EBV DNA level was reported by our previous study 18 , The cutoff value for pretreatment EBV DNA level (pre-EBV DNA) was set at 5000 copies/mL, which was calculated by receiver operator characteristic (ROC) curve analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information on chemotherapy, radiotherapy, measurements of EBV DNA level and tumor volumes was reported in our previous study 19 and is also shown in the Supporting Information materials.…”
Section: Methodsmentioning
confidence: 99%